1990
DOI: 10.1042/cs0780127
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure, left ventricular mass and intracellular calcium in primary hyperparathyroidism

Abstract: 1. Blood pressure, left ventricular mass and platelet cytosolic free calcium concentrations were measured in 23 patients with untreated primary hyperparathyroidism, 30 normotensive control subjects and 23 control subjects matched for age, sex and blood pressure. In 12 patients measurements were repeated after parathyroidectomy. 2. Patients with primary hyperparathyroidism had significantly elevated blood pressures (139 +/- 6/86 +/- 3 mmHg, mean +/- SEM) compared with control subjects (125 +/- 2/78 +/- 1 mmHg),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
8

Year Published

1991
1991
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 25 publications
(8 reference statements)
2
31
0
8
Order By: Relevance
“…According to some authors, this prevalence may vary from 20 to 80%. [2][3][4][5] The results of our study confirm and extend these data reported in the 30,31 (c) renal function injury; 7,8 (d) activation of the renin-angiotension-aldosterone system; [32][33][34] (e) activation of the sympathetic nervous system; 26,29 (f) activation of the endothelin 35 and adrenomedullin 36 systems.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…According to some authors, this prevalence may vary from 20 to 80%. [2][3][4][5] The results of our study confirm and extend these data reported in the 30,31 (c) renal function injury; 7,8 (d) activation of the renin-angiotension-aldosterone system; [32][33][34] (e) activation of the sympathetic nervous system; 26,29 (f) activation of the endothelin 35 and adrenomedullin 36 systems.…”
Section: Discussionsupporting
confidence: 83%
“…Further- Table 6 What is known on this topic K The prevalence of arterial hypertension has been shown to be higher in PHPT than in general population: the prevalence may vary from 20 to 80% [2][3][4][5] K Calcium was studied as a factor responsible for the pathogenesis of hypertension in PHPT 4 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Parathormone (PTH) and vitamin D are the major calcitropic hormones, and the levels of these two hormones have been reported to vary in patients with essential hypertension (11). In several studies, a relationship between hyperparathyroidism with LVH and BP elevation has been demonstrated in hypertensive patients (1,(12)(13)(14). However, whether the increase in PTH level is the result of or the reason for the BP elevation has not been elucidated (15).…”
Section: Introductionmentioning
confidence: 99%